Experience of an information aid for newly diagnosed multiple sclerosis patients: a qualitative study on the SIMS‐Trial. (1st November 2011) - Borreani, Claudia; Giordano, Andrea; Falautano, Monica; Lugaresi, Alessandra; Martinelli, Vittorio; Granella, Franco; Tortorella, Carla; Plasmati, Imma; Radaelli, Marta; Farina, Deborah; Dalla Bella, Eleonora; Bianchi, Elisabetta; et al.
Abstract Background The SIMS‐Trial (ISRCTN81072971) proved the effectiveness, in terms of patient's knowledge and care satisfaction, of an add‐on information aid (personal interview with a physician using a navigable CD and take‐home booklet) in 120 newly diagnosed patients with multiple sclerosis (MS) from five Italian centres. Objective To scrutinize the experience of SIMS‐Trial participants in order to gain better understanding of the effectiveness of the information aid and its components. Design We performed (i) nine individual semi‐structured interviews with a purposeful sample of SIMS‐Trial patients who received the information aid, (ii) focus group meeting (FGM) with the physicians who conducted the personal interview, and (iii) FGM with patients' caring neurologists. Results Patients' experience with the information aid was positive as it enhanced their understanding of their disease, being viewed as a guided tour of their medical condition. The physicians who conducted the personal interviews were also positive in their overall evaluation but noted an initial difficulty in using the CD. The caring neurologists had limited direct experience of the aid, and their views were confined to utility of the information aid in general. All participants considered the combination of personal interview, CD navigation and take‐home booklet essential, but urged a more flexible scheduling of the personal interview. It also emerged that some content required revision and that the aid was unsuitable for patients with primary progressive MS. Conclusions The results of the study further support the value of the aid and also provide important indications for improving it and refining indications for use.